A study of a Visitor Counter with automated entry and exit - Chattopadhyay, Adriza; Mukherjee, Belonia; Rudra, Pritha; Chakraborty, Debraj (International Journal of Computer Sciences and Engineering, 2025)
The model discussed here is a bidirectional visitor counter .The key features described in the model are i) counting number of people entering and exiting a room using an embedded system ii) using the concept of Infra Red sensor modules (TSOP sensor) and servo motors.[1]The embedded system used here is an Arduino Uno board. It is a microcontroller (Atmega328) based board having 14 digital pins (out of which some are PWM pins) and 6 analog pins. The Arduino have been programmed using EMBEDDED C. The detection of people entering or leaving is done by the IR modules. The concept of servo motor has been used for the opening and closing of the gates at the entrance and exit. Finally the entire counting process is done by the arduino and the final number of people inside the room at a particular instant of time is displayed in the serial monitor of the Arduino IDE (Arduino programming Interface) and can be seen using a laptop or personal computer.